Secondary involvement of Meckel's diverticulum by group A β-hemolytic streptococcus in a child with upper airways infection treated by laparoscopic-assisted resection. Issue 2 (April 2015) - Bertozzi, Mirko; Verrotti, Alberto; Latini, Maria Elena; Rinaldi, Victoria Elisa; Di Cara, Giuseppe; Appignani, Antonino
<x xml:space="preserve">Abstract</x> We report a case of a 5-year-old boy with acute abdomen following an upper airways infection who developed Meckel's diverticulum perforation secondary to group A β-hemolytic streptococcus and its successful treatment by a laparoscopic-assisted intervention. To the best of our knowledge, such an event has never been reported previously.